ASSESSMENT OF PROFILE AND QUALITY OF LIFE OF ELDERLY PEOPLE WITH ELIMINATION OSTOMIES (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objective: The aim of this study was to assess the epidemiological profile and quality of life of elderly people with elimination ostomy in a health region in Minas Gerais. Methods: This is a cross-sectional study carried out in a public health care service. To describe the profile, all medical records of elderly people with ostomy were evaluated. Then, quality of life was assessed using the City of Hope-Quality of Life-Ostomy Questionnaire. Results: There was a mostly female population (55.2%) with a mean age of 67 years (± 8.8). In 64%, the ostomies were definitive, with colorectal cancer being the main diagnosis (71%) and in 41.4% they were partially dependent on self-care. Regarding the assessment of quality of life, the domains of spiritual, physical and social well-being had better assessment indicators (8.1; 8.1; and 8.2 respectively). It was evident that the type of ostomy and the length of stay are negatively associated with the quality of life of people with ostomies. Conclusion: The quality of life of elderly people with an elimination ostomy was well evaluated, especially in the domains of physical, social and spiritual well-being.